Do Department of Justice Intervention and Citizen Oversight Improve Police Accountability?, United States, 1995-2019 - Adams, Terri M. ([Verlag nicht ermittelbar], 2023)
The data in this study assess police misconduct by considering civilian review boards (CRBs) and federal intervention by the United States Department of Justice (DOJ). The latter involves civil rights investigations of alleged pattern-or-practice violations that resulted in consent decrees or memoranda of agreement under 42 USC 14141 (re-codified in 2017 as 34 USC 12601) of the Violent Crime Control and Law Enforcement Act of 1994 (1994 Crime Bill); technical assistance letters based on the outcome of DOJ investigations, which lead to voluntary reforms; and requests for assistance from the Office of Community Oriented Policing Services (COPS).